2009
DOI: 10.1002/cphc.200900122
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of Iodoform in Methanol: Formation and Fate of the Iso‐CHI2‐I Photoproduct

Abstract: Ultrafast population and structural dynamics due to the iso-CHI(2)-I isomer product formed upon UV excitation of iodoform (CHI(3)) in solution is monitored by femtosecond transient absorption with deep-UV through near-IR probing and picosecond transient resonance Raman spectroscopy. Iso-CHI(2)-I is found to be a major photochemical product regardless of excitation wavelength (266 and 350 nm) and choice of solvent (methanol, acetonitrile, and cyclohexane), and is produced in 50% quantum yield upon 266 nm excita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 35 publications
4
40
1
Order By: Relevance
“…Compared with the UV-visible pump-probe experiments, these are more difficult to interpret, but are sensitive to structures that are blind to optical probes. This result was 346 S.A. Reid apparently in conflict with earlier time-resolved TA and Raman experiments [73,95]; however, a subsequent ultrafast TA study showed that iso-CHI 3 reacted readily with the solvent (methanol) to eliminate HI [83]. The absence of evidence for formation of the iso-CBr 4 species led these authors to conclude that isomer formation represented a minor channel.…”
Section: Sa Reidmentioning
confidence: 85%
“…Compared with the UV-visible pump-probe experiments, these are more difficult to interpret, but are sensitive to structures that are blind to optical probes. This result was 346 S.A. Reid apparently in conflict with earlier time-resolved TA and Raman experiments [73,95]; however, a subsequent ultrafast TA study showed that iso-CHI 3 reacted readily with the solvent (methanol) to eliminate HI [83]. The absence of evidence for formation of the iso-CBr 4 species led these authors to conclude that isomer formation represented a minor channel.…”
Section: Sa Reidmentioning
confidence: 85%
“…4,[25][26][27] Cage-enhanced geminate recombination has significant yield to the iso products and these products have been observed in variety of different experiments. 3,25,26,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Ultraviolet excitation of CH 2 BrI yields iso-CH 2 Br-I or iso-CH 2 I-Br following C-I or C-Br bond cleavage, respectively. These products are predicted to have transitions in the visible or near UV with very large oscillator strength (∼0.5).…”
Section: Introductionmentioning
confidence: 99%
“…Here, photolysis is known to lead to facile production of the iso-halomethanes following geminate recombination of the initially formed radical pair in the solvent cage, and the isomers have been shown to play a pivotal role in the reactivity of halomethanes in solution. [40][41][42][43][44][45][46][47][48][49][50][51][52][53] For example, iso-CH 2 I 2 is the primary species responsible for the FIG. 1.…”
Section: Introductionmentioning
confidence: 99%